2017
DOI: 10.1080/07435800.2017.1373662
|View full text |Cite
|
Sign up to set email alerts
|

Role of sclerostin and dkk1 in bone remodeling in type 2 diabetic patients

Abstract: The sclerostin and dkk1 levels increased in conjunction with the reduction of BMD, confirming that the Wnts, inhibited by sclerostin and dkk1, were potentially responsible for bone fragility in type 2 diabetes patients with osteoporosis. Note that the serum sclerostin levels were predictors for bone formation, while the DKK1 levels predicted bone resorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 47 publications
3
20
1
Order By: Relevance
“…We found that serum sclerostin was higher in patients with combined T2DM and osteoporosis than osteoporosis only; the biomarker was positively correlated with higher degrees of osteoporosis-as indicated by BMD-as well as markers of insulin resistance and glycemic control. Similar to our ndings, Wang and colleagues (33) showed that the combination of T2DM and osteoporosis led to higher increase in serum sclerostin than osteoporosis alone; moreover, serum sclerostin correlated with BMD parameters, HbA1c, and serum glucose level. Likewise, García-Martín and colleagues (34) found positive correlation between with higher severity of osteoporosis, HOMA-IR, and serum insulin.…”
Section: Discussionsupporting
confidence: 89%
“…We found that serum sclerostin was higher in patients with combined T2DM and osteoporosis than osteoporosis only; the biomarker was positively correlated with higher degrees of osteoporosis-as indicated by BMD-as well as markers of insulin resistance and glycemic control. Similar to our ndings, Wang and colleagues (33) showed that the combination of T2DM and osteoporosis led to higher increase in serum sclerostin than osteoporosis alone; moreover, serum sclerostin correlated with BMD parameters, HbA1c, and serum glucose level. Likewise, García-Martín and colleagues (34) found positive correlation between with higher severity of osteoporosis, HOMA-IR, and serum insulin.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, we and others demonstrated that serum and skeletal levels of DKK1, but not SOST, are elevated in obese mice and in patients with type 2 diabetes mellitus . As DKK1 is a potent suppressor of bone formation and bone mass, we hypothesized that elevated DKK1 levels may drive obesity‐induced bone loss in mice.…”
Section: Introductionmentioning
confidence: 92%
“…In our meta-analysis we also found increased levels of circulating sclerostin in patients with T2D compared with controls [ 25 ]. Circulating levels of sclerostin have previously been associated with low BMD and also correlated negatively with circulating levels of PINP in patients with T2D [ 30 ]. Sclerostin is produced by the osteocytes and regulate bone turnover by being an antagonist of the Wnt pathway [ 31 ].…”
Section: Low Bone Turnover In Diabetic Bone Diseasementioning
confidence: 99%